A new species of Nilothauma Kieffer from China, with a key to known species of the genus (Diptera: Chironomidae) - Qi, Xin; Lin, Xiaolong; Wang, Xinhua; Shao, Qingjun (Zootaxa, 2014)
A new species of the genus Nilothauma Kieffer, N. pandum sp. n., is described, and its morphological descriptions and illustrations are also given. A key to the males of Nilothauma is given. The adult male of N. pandum sp. n. can be distinguished from known species of the genus by the following combination of characters: anal point very broadly lanceolate with microtrichia in median ridge and apical margin, rounded at apex; superior volsella pad-like, expanded distally; median volsella curved, rounded at apex, with 2 long basal setae and 1 long median seta.